2011
DOI: 10.1088/0953-4075/45/2/025501
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the repetition rate of a mode-locked laser using anf-deformed Bose–Einstein condensate

Abstract: Investigations are made for the possibility of using an f -deformed Bose-Einstein condensate (BEC) inside the resonator of a mode-locked laser to achieve tunable control of the repetition rate. Slow light propagation of the probe field through the f -deformed BEC may lead to a large observable increase in the cavity round-trip delay and, therefore, to a reduction in the effective repetition rate of the laser. Conversely, negative propagation velocity through the f -deformed BEC can lead to a decrease in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To aim at higher intensities and amplification factors, the nonlinear response of the atomic gas should also be taken into account. Denser condensates, with a nonlinear response and quantum corrections, including atomatom interactions, but without local field correction, seem to be beneficial for larger delay times as well [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To aim at higher intensities and amplification factors, the nonlinear response of the atomic gas should also be taken into account. Denser condensates, with a nonlinear response and quantum corrections, including atomatom interactions, but without local field correction, seem to be beneficial for larger delay times as well [15].…”
Section: Discussionmentioning
confidence: 99%
“…The promise of laser pulse amplification by atomic condensates is further studied by taking into account atom-atom interactions in an f-deformed condensate formalism very recently [15]. It is found that interactions make the amplification effect stronger.…”
Section: Introductionmentioning
confidence: 99%